2016
DOI: 10.1007/s00181-016-1209-y
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting carbon Kuznets curves with endogenous breaks modeling: evidence of decoupling and saturation (but few inverted-Us) for individual OECD countries

Abstract: This paper tests for a carbon Kuznets curve (CKC) by examining the carbon emissions per capita-GDP per capita relationship individually, for 21 OECD countries over 1870-2010 using a reduced-form, linear model that allows for multiple endogenously determined breaks. This approach addresses several important econometric and modeling issues, e.g., (i) it is highly flexible and can approximate complicated nonlinear relationships without presuming a priori any particular relationship; (ii) it avoids the nonlinear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Although Chudik et al (2011) and Pesaran and Tosetti (2011) found that the CCEMG approach performed well with moderate and robust elements, it also demonstrated they could deal effectively with a wide range of global statistical shocks, such as oil price spillover effects and monetary concerns. CCEMG also has the advantage of removing spillover effects by considering the averages of both dependent and independent determinants that occur as a result of cross-sectional dependence (Liddle & Messinis, 2018). The technique of AGM, on the other hand, is an alternative approach to the CCEMG because, according to Eberhardt and Teal (2010), after dealing with the issues of heterogeneity, CD, and structural breaks, it also settles the time framework and deals with the unobservable elements of the data and considers this act as a dynamic process.…”
Section: Robustness Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Chudik et al (2011) and Pesaran and Tosetti (2011) found that the CCEMG approach performed well with moderate and robust elements, it also demonstrated they could deal effectively with a wide range of global statistical shocks, such as oil price spillover effects and monetary concerns. CCEMG also has the advantage of removing spillover effects by considering the averages of both dependent and independent determinants that occur as a result of cross-sectional dependence (Liddle & Messinis, 2018). The technique of AGM, on the other hand, is an alternative approach to the CCEMG because, according to Eberhardt and Teal (2010), after dealing with the issues of heterogeneity, CD, and structural breaks, it also settles the time framework and deals with the unobservable elements of the data and considers this act as a dynamic process.…”
Section: Robustness Testmentioning
confidence: 99%
“…However, other independent variables are denoted by t (G i,t ). Furthermore, the average cross-sectional (X) is used to avoid the spillover effect produced by the presence of crosssectional dependence (Liddle & Messinis, 2018).…”
Section: The (Cs-ardl) Techniquementioning
confidence: 99%
“…This substantial evidence of inverted-Us for sulfur provides an interesting contrast to Liddle and Messinis (2014), who analyzed the income-carbon relationship for OECD countries employing the same methods used here. Liddle and Messinis found evidence of inverted-Us for carbon for only four of the 23 OECD countries they considered.…”
Section: Resultsmentioning
confidence: 79%
“…Many others have highlighted similar trends, including (recently) Hatfield-Dodds et al (2015) for Australia; Apergis (2016) for 15 OECD countries during 1960OECD countries during -2013Shuai et al (2017) for a panel of 164 countries; Liddle and Messinis (2018) for 21 OECD countries (during 1870-2010); Apergis, Christou, and Gupta (2017) for U.S. states; and Wagner, Grabarczyk, and Hong (2020) for Austria, Belgium, Finland, the Netherlands, Switzerland and the U.K. 5 Likewise, the International Energy Agency (IEA) has argued-albeit on the basis of just three years of data 2014-2016-that global carbon emissions (which remained stable) have decoupled from economic growth (IEA 2016). The World Resources Institute, a climate think-tank based in Washington D.C., reports that as many as 21 countries (mostly belonging to the OECD) managed to reduce their (territorial) carbon emissions while growing their GDP in the period 2000 to 2014 (Aden 2016); these 21 countries should be role models for the rest of the world.…”
mentioning
confidence: 85%